If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -7) + 2(2x + 17) = 5(3x + -4) + 37 Reorder the terms: 3(-7 + 5x) + 2(2x + 17) = 5(3x + -4) + 37 (-7 * 3 + 5x * 3) + 2(2x + 17) = 5(3x + -4) + 37 (-21 + 15x) + 2(2x + 17) = 5(3x + -4) + 37 Reorder the terms: -21 + 15x + 2(17 + 2x) = 5(3x + -4) + 37 -21 + 15x + (17 * 2 + 2x * 2) = 5(3x + -4) + 37 -21 + 15x + (34 + 4x) = 5(3x + -4) + 37 Reorder the terms: -21 + 34 + 15x + 4x = 5(3x + -4) + 37 Combine like terms: -21 + 34 = 13 13 + 15x + 4x = 5(3x + -4) + 37 Combine like terms: 15x + 4x = 19x 13 + 19x = 5(3x + -4) + 37 Reorder the terms: 13 + 19x = 5(-4 + 3x) + 37 13 + 19x = (-4 * 5 + 3x * 5) + 37 13 + 19x = (-20 + 15x) + 37 Reorder the terms: 13 + 19x = -20 + 37 + 15x Combine like terms: -20 + 37 = 17 13 + 19x = 17 + 15x Solving 13 + 19x = 17 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 13 + 19x + -15x = 17 + 15x + -15x Combine like terms: 19x + -15x = 4x 13 + 4x = 17 + 15x + -15x Combine like terms: 15x + -15x = 0 13 + 4x = 17 + 0 13 + 4x = 17 Add '-13' to each side of the equation. 13 + -13 + 4x = 17 + -13 Combine like terms: 13 + -13 = 0 0 + 4x = 17 + -13 4x = 17 + -13 Combine like terms: 17 + -13 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 | | Y=5x^2+35 | | z-34.7=68.2 | | 10x+8y+z=100 | | 6x-30=6x+12 | | 5ln(x^2)=4ln(x^3)+6 | | 3x^2-11=37 | | Cry+z=9fory | | y(y-12)+y-12=0 | | 12X+2=76 | | 12X+2=78 |